Bibliometric Analysis of the Creative Economy: Exploring Key Themes and Research Developments - Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2024)
This study utilizes bibliometric analysis and network visualizations to examine the evolution and current state of creative economy research over the past two decades. By analyzing keyword co-occurrence and co-authorship networks, we identify central themes and trace collaborative patterns among researchers globally. Our findings highlight the critical roles of urban planning, sustainability, and economic development as recurring focal points within the creative economy discourse. International collaboration networks further reveal the United States, United Kingdom, and Germany as central hubs, facilitating significant scholarly exchange and driving research innovations. Temporal trends in publication volumes exhibit a marked growth in interest until 2022, followed by a slight decline, suggesting a phase of consolidation in the field. This study underscores the importance of creative industries in urban and regional development and points towards the necessity for innovative research approaches in the post-pandemic era, emphasizing technology integration and sustainability.